2022
DOI: 10.1556/2006.2022.00005
|View full text |Cite
|
Sign up to set email alerts
|

Getting “clean” from nonsuicidal self-injury: Experiences of addiction on the subreddit r/selfharm

Abstract: Background & Aims Previous studies have shown that nonsuicidal self-injury (NSSI) has addictive features, and an addiction model of NSSI has been considered. Addictive features have been associated with severity of NSSI and adverse psychological experiences. Yet, there is debate over the extent to which NSSI and substance use disorders (SUDs) are similar experientially. Methods To evaluate the extent that people who self-injure experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Indeed, one study investigated one of the key symptoms of the addictive process, namely craving, and showed that this construct was more central for substance use disorder than for NSSI [30]. Furthermore, the use of terms referring to addictive behaviors by participants can be interpreted as a way of reducing the stigma around NSSI, while implying that recovery would be possible [31]. Further studies are needed to clarify the similarities and differences in process between addictive behaviors and NSSI.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, one study investigated one of the key symptoms of the addictive process, namely craving, and showed that this construct was more central for substance use disorder than for NSSI [30]. Furthermore, the use of terms referring to addictive behaviors by participants can be interpreted as a way of reducing the stigma around NSSI, while implying that recovery would be possible [31]. Further studies are needed to clarify the similarities and differences in process between addictive behaviors and NSSI.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, craving for NSSI was significantly lower compared to drug craving and was typically reported in the context of negative emotions, while craving for drugs was reported in a wide variety of emotional states. However, we should also mention that when analyzing the internet posts of people who engaged in NSSI, the addiction potential of NSSI has been clearly demonstrated ( 43 ). The most indicative SUDs criterion was urge/craving in reference to NSSI.…”
Section: Introductionmentioning
confidence: 99%
“…The most indicative SUDs criterion was urge/craving in reference to NSSI. Moreover, the user-level addictive characteristics of NSSI are closely linked to more serious versatility and more associated psychiatric disorders ( 43 ). It is also worth noting that there are attempts to treat addiction-type experiences of NSSI as a behavioral addiction.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the proximal and dynamic drivers of NSSI urge fluctuation is likely to aid the identification of novel intervention targets. NSSI episodes are triggered by negative affect (Kiekens et al, 2020) and are preceded by thoughts and urges that intensify over time (Himelein-Wachowiak et al, 2022;Miller et al, 2021), typically over a duration of approximately 30 min (Fitzpatrick et al, 2020). Interestingly, while urge intensity is a strong proximal predictor of NSSI behavior (Ammerman et al, 2017;Turner et al, 2019), negative affect (Kiekens et al, 2020) and persistent ideation do not appear to be strong predictors of behavior (Turner et al, 2019).…”
mentioning
confidence: 99%